Nicaragua: Red de Protección Social - Mi Familia: breaking the cycle of poverty - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
"In its first two years, 2000–02, the Red de Protección Social — Ministry of the Family (RPS) improved the nutrition and education of approximately 10,000 of Nicaragua’s poorest families. Operating as a pilot project in six municipalities in Matagalpa and Madriz, RPS could claim: (1) Substantial increases in family purchasing power—up to 40 percent for the extremely poor — with most of the spending going toward more and better food; (2) A one-third reduction in the extreme-poverty rate; (3) A reduction of 5 percentage points in the incidence of children under five who are stunted (few programs in the world have seen this level of improvement in only two years); (4) A nearly 20 percentage point rise in enrollment rates for primary school children; and (5) The child-labor rate cut in half in program areas." -- From Text